Green’s functional for higher-order ordinary differential equations with general nonlocal conditions and variable principal coefficient - Özen, K. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
The method of Green’s functional is a little-known technique for the construction of fundamental solutions to linear ordinarydifferential equations (ODE) with nonlocal conditions. We apply this technique to a higher order linear ODE involvinggeneral nonlocal conditions. A novel kind of adjoint problem and Green’s functional are constructed for the completelyinhomogeneous problem. Several illustrative applications of the theoretical results are provided.